Apoptosis: Mechanisms of Programmed Cell Death and its Biological Significance - Parasuraman, Subramani; Madhavrao, Chavan; BK, Mythili (Free Radicals and Antioxidants, 2025)
Apoptosis is a highly regulated, genetically programmed form of cell death essential for maintaining homeostasis in multicellular organisms. Unlike necrosis, which involves cell swelling and inflammatory rupture, apoptosis is characterized by distinct morphological features, including cell shrinkage, chromatin condensation, nuclear fragmentation, and the formation of membrane-bound apoptotic bodies. This process is primarily orchestrated through the intrinsic and extrinsic pathways, both of which culminate in a proteolytic cascade involving initiator and executioner caspases. The biological significance of apoptosis spans embryonic development, immune system regulation, and the elimination of damaged or virus-infected cells. Efficient phagocytosis of apoptotic remains, or efferocytosis, ensures tissue renewal without an inflammatory response. Dysregulation of these pathways is central to various pathologies, including cancer, autoimmune disorders, and neurodegenerative diseases. This review summarizes the morphological and biochemical mechanisms of the intrinsic and extrinsic pathways and evaluates their biological significance for tissue homeostasis and disease pathology.
Keywords: Apoptosis; Caspases; Extrinsic Pathway; Homeostasis; Intrinsic Pathway